2013
DOI: 10.1093/eurjhf/hfs197
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adaptive servo‐ventilation on cardiovascular function and prognosis in heart failure patients with preserved left ventricular ejection fraction and sleep‐disordered breathing

Abstract: AimsEffective pharmacotherapy for heart failure with preserved left ventricular ejection fraction (HFpEF) is still unclear. Sleep-disordered breathing (SDB) causes cardiovascular dysfunction, giving rise to factors involved in HFpEF. However, it remains unclear whether adaptive servo-ventilation (ASV) improves cardiovascular function and longterm prognosis of patients with HFpEF and SDB. Methods and resultsThirty-six patients with HFpEF (LVEF .50%) and moderate to severe SDB (apnoea -hypopnoea index .15/h) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
87
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 37 publications
3
87
0
4
Order By: Relevance
“…Additionally, meta‐analysis has demonstrated that continuous positive airway pressure improves aortic stiffness in patients with OSA 40. We previously reported that the reduction of all‐cause mortality in HFpEF patients with SDB after positive airway pressure treatment might be partly due to improvement of aortic stiffness 41, 42. Thus, it is possible to speculate that SDB management using positive airway pressure improves the prognosis of HFpEF patients via a decrease in arterial stiffness, which is one of the important mechanisms underlying HFpEF, as we reported in our previous study.…”
Section: Discussionsupporting
confidence: 61%
“…Additionally, meta‐analysis has demonstrated that continuous positive airway pressure improves aortic stiffness in patients with OSA 40. We previously reported that the reduction of all‐cause mortality in HFpEF patients with SDB after positive airway pressure treatment might be partly due to improvement of aortic stiffness 41, 42. Thus, it is possible to speculate that SDB management using positive airway pressure improves the prognosis of HFpEF patients via a decrease in arterial stiffness, which is one of the important mechanisms underlying HFpEF, as we reported in our previous study.…”
Section: Discussionsupporting
confidence: 61%
“…18 Furthermore, Yoshihisa et al reported that ASV therapy improved the long-term prognosis of patients with chronic HF and CSR for about 3 years, and that of patients with HF, preserved LVEF, and SDB for about 4 years. 10,19 Similar research also suggested that ASV therapy could improve the prognosis of patients with HF and comorbid chronic kidney disease and SDB. 20 However, the present report differs from those reports 10,[18][19][20] in that we evaluated the relationship between longterm prognosis and SDB severity.…”
Section: Findings and Data Interpretationmentioning
confidence: 88%
“…10,19 Similar research also suggested that ASV therapy could improve the prognosis of patients with HF and comorbid chronic kidney disease and SDB. 20 However, the present report differs from those reports 10,[18][19][20] in that we evaluated the relationship between longterm prognosis and SDB severity. Indeed, we found improved long-term prognosis regardless of SDB severity in a larger cohort (n = 61) than previously reported.…”
Section: Findings and Data Interpretationmentioning
confidence: 88%
See 1 more Smart Citation
“…Several studies suggest that ASV is more effective than CPAP, bi -level pressure support ventilation, or increased dead space in alleviating CSA 36 -39) . We demonstrated that ASV improves not only left ventricular systolic 40 -42) and diastolic function 43) , but also pulmonary function 27) , renal function 44) , vascular function 43) , as well as prognosis in HF patients with reduced or preserved EF 27,40 -44) . Recent meta -analyses on ASV in HF patients with CSA suggested an overall improvement in CSA, as well as improvements in LVEF, diastolic dimensions and function, 6 -min walk test distance, plasma natriuretic peptide concentration, and sympathetic activity 2,45) .…”
mentioning
confidence: 80%